(untitled) (Research, Society and Development, 2022)
Objective: To analyze the scientific evidence on the effective methods used by nurses to prevent pressure injuries in the intensive care unit. Methodology: This is an Integrative Literature Review, developed between November 2021 and March 2022, in the Virtual Health Library and CAPES (Coordination for the Improvement of Higher Education Personnel), through the descriptors Pressure Injury, ICU and Prevention, using the full text filters available; document type: scientific articles; Portuguese language; year of publication 2017 to 2022. Thus, based on the methodological quality assessment, a sample of 14 articles was established. Results and Discussions: According to the protocol of the Ministry of Health, the main preventive measures carried out by nurses are the assessment of patients at risk; the management of nutritional status including hydration, inspection and daily assessment of the skin; moisture management and pressure redistribution. Conclusion: Nurses act as the main promoters of the prevention of health problems in different sectors. Some authors reaffirm the importance of this professional in the face of quality care and the development of practices capable of minimizing the incidence of infections according to their interventions, always aiming at actions to prevent all avoidable complications in the ICU.